Comprehending the Metaphysical Framework in St. Augustine's Moral Philosophy: An Analytical Inquiry - Prahasan, Marimuthu (South Asian Journal of Social Sciences and Humanities, 2024)
Saint Augustine stands as a towering figure within the history of Western philosophical thought, having crafted a unique and influential religious-philosophical paradigm that integrates diverse intellectual currents including Manichaeism, Neo-Platonism, ancient moral philosophies, and Christian theology. Through this syncretic approach, Augustine offers a comprehensive framework for understanding the human condition and the pursuit of spiritual fulfillment. Central to Augustine's philosophical edifice are a series of interwoven metaphysical concepts that form the backbone of his thought. These include the nature of divinity, the origins of the cosmos, the essence of the human soul, the problem of evil, and the nature of free will, etc. Augustine synthesizes these notions into a coherent vision of human existence, wherein individuals are guided towards a life of moral integrity and spiritual ascent. One of Augustine's distinctive insights is his conception of governance and ruler-ship as divine mandates imbued with metaphysical significance. According to Augustine, earthly authorities are entrusted by God with the responsibility of protecting the faithful and upholding moral order within society. Consequently, he argues for the legitimacy of defensive warfare as a means of safeguarding the righteous against external threats. Furthermore, Augustine develops a nuanced epistemological stance to underpin his theological assertions, thus fortifying them against potential philosophical challenges. Through a qualitative inquiry grounded in secondary sources, this study seeks to elucidate the intricate interplay between metaphysical ideals and various aspects of human well-being, governmental legitimacy, and the moral justifications for defensive warfare. By exploring Augustine's intellectual legacy in depth, this research aims to shed light on the enduring relevance of his thought in contemporary philosophical discourse.
Keywords: Saint Augustine; Metaphysics; Ethics; Just War; Original Sin